Cognitive and Educational Effects of the Elkonin—Davydov System of Developmental Education: Opportunities and Limitations - Gordeeva T.O. (Культурно-историческая психология, 2020)
The Elkonin—Davydov system of developmental education has come a long way, from an experimental program to widespread recognition in elementary schools in Russia. The article is dedicated to the analysis of studies devoted to evidence of the effectiveness of the developmental education system in terms of cognitive development and the formation of educational activities. Four main categories of results were identified, according to which the publications were found and analyzed: differences between children from developmental and so-called traditional classes in the level of theoretical thinking; general cognitive development and intelligence; educational strategies and the ability to solve non-standard problems; traditional educational achievements. The analysis allows to conclude that the developmental education system has a significant potential in relation to the development of theoretical thinking of schoolchildren, the ability to learn independently and solve non-standard problems. On the contrary, schoolchildren from developmental education classes do not differ from schoolchildren in traditional education classes in terms of the level of empirical thinking, as well as in terms of learning indicators related to solving standard problems and demonstrating knowledge and skills required by the school curriculum. The author analyzes the limitations of the studies, including their cross-sectional, non-longitudinal nature, lack of measurement before the start of education, specificity of samples (the majority of them being based on material from school-laboratories), shortcomings in the description of the results. The possible reasons for the heterogeneity of the results are also discussed. The analysis allows to conclude that the system of developmental education offers scientifically based and approved pedagogical technology that promotes the gradual “cultivation” in schoolchildren the theoretical thinking, thinking skills and development of the ability to acquire new knowledge.